THE EFFECT OF A SELF-SUPERVISION MODEL BASED ON AUTHENTIC MOVEMENT AND EPIMOTORICS' ON EMOTION-RELATED PHYSIOLOGICAL PARAMETERS AMONG DANCE MOVEMENT THERAPISTS - Yifat SHALEM-ZAFARI; Emilia Florina GROSU (Cluj University Press, 2018)
Introduction: This is part of a larger study examining the effects of an original self-supervision model (SSM), based on Authentic Movement and Epimotorics', on novice dance movement therapists. The larger study examines movement parameters, psychological parameters, and physiological measures, while the present study focuses on the emotion-related physiological parameters of pulse and oxygen saturation. Used regularly in medical settings, these have also been found to reliably reflect a person's emotional state (Appelhans & Luecken, 2006; Porges, 2007; Picard, 1997). Objective: To see whether the SSM training affects participants' pulse and oxygen saturation. The hypothesis is that there will be a decrease in pulse variables and increase in oxygen saturation after the SSM training, which would reflect lower emotional arousal and stress. Methods and Materials: Pulse oximetry was used to measure pulse and oxygen saturation. These were recorded before and after a simulation at the start of the SSM training, and before and after a simulation at the end of the training. To detect changes in pulse variables according to the time of measurement (before and after each simulation), a series of paired-samples t-tests was performed: The first series compared the 'after' measurements of both simulations. The second series compared the 'before' measurement of Simulation 1 to the 'after' measurement of Simulation 2. Results: The training affected all measures, showing a significant decrease in pulse variables in Simulation 2 (after) compared to the beginning of Simulation 1 (before). Conclusion: The results suggest that the SSM decreases stress, as reflected in decreased pulse variables.